THE PORTRAYAL AND THE CONSEQUENCE OF TRACY WHITNEY’S ABSURDITY IN “IF TOMORROW COMES” BY SIDNEY SHELDON - Purnamasari, Lidia Ayu (Srawung: Journal of Social Sciences and Humanities, 2022)
This study aims to describe about the portrayal and the consequence of the absurdity in Tracy Whitney’s life in If Tomorrow Comes novel written by Sidney Sheldon. Tracy Whitney is described as a free and an independent woman who had a perfect life. However, the perfect life is suddenly changed into miserable life. She is being trapped by the gang of mafia in her town and nobody cares for her. This study used descriptive qualitative as the methodology with library research as the approach of the study. Albert Camus’ absurdism theory is also used as the main theory in analyzing the literary work. The result shows that the life of the main character that suddenly changes from harmonious life into miserable life is found as an absurd situation. The feeling of hopelessness and alienated makes the life of the main character becomes absurd. Moreover, in the consequence from the absurd situation the main character chooses to revolt and and accepting her condition.